Revenue-maximizing Top Earned Income Tax Rate in the Presence of Income-shifting - Kaisa Kotakorpi; Tuomas Matikka (De Gruyter, 2022)
We provide an analysis of the revenue-maximizing top earned income tax rate for a country with one of the highest levels of earnings taxation in the world, Finland, and compare it to the current level of taxation. We account for the effect of income-shifting possibilities in the calculations and find that the current top tax rate on earnings in Finland is likely to be below the revenue-maximizing rate. We provide an explicit account of assumptions behind the Laffer curve calculations and demonstrate that policy conclusions depend critically on non-trivial choices regarding, for example, how the current top tax rate is calculated. The assumptions in the Laffer curve calculations need to be made explicit if the calculations are to provide guidance for policy.